Pemberdayaan dan Kepedulian Sosial melalui Kegiatan Pembagian Sembako dan Pakaian Bekas Layak Pakai kepada Masyarakat - Mufaizah Mufaizah; Najwa Zuhrotul Auliya; Rahayu Mardikaningsih; Didit Darmawan; Muhammad Iqbal Maududi (Universitas Pahlawan Tuanku Tambusai, 2026)
The distribution of basic food supplies and used clothing in good condition by students of Universitas Sunan Giri Surabaya is a manifestation of social care to alleviate the financial burden of underprivileged communities. This activity aims to build solidarity and trust as the foundation for more equitable social relations. Through a direct and participatory approach using the Asset-Based Community Development (ABCD) method, this activity successfully created positive interactions and taught students about social responsibility and empathy. The analysis shows that similar programs can achieve sustainability by involving the community in planning and collaborating with local stakeholders. The results prove that this intervention not only meets basic needs but also serves as an initial bridge to build trust, empathy, and social awareness among students. The main recommendation is to transform incidental aid into a sustainable empowerment program based on participation and community rights, aiming for economic and social independence.